2022
DOI: 10.3390/ijms231810943
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 25-Hydroxy-Vitamin D in Human Macrophages Is Highly Dependent on Macrophage Polarization

Abstract: Macrophages synthesize active vitamin D (1,25-dihydroxy-vitamin D) and express the vitamin D receptor in the nucleus; however, vitamin D metabolism in relation to macrophage polarization and function is not well understood. We studied monocyte-derived macrophages (MDMs) from human buffy coats polarized into M0, M1 (LPS + IFNγ), M2a (IL4 + IL13) and M2c (IL10) macrophage subtypes stimulated with 25-hydroxy-vitamin D (1000 and 10,000 nanomolar). We measured vitamin D metabolites (25-hydroxy-vitamin D, 1,25-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The presented results provide evidence that both catabolic pathways, via 24-hydroxylase enzyme into 24,25(OH) 2 D and 1,24,25(OH) 3 D, considered as inert metabolites, and via C3-epimerase catabolic pathway [ 22 , 23 ] resulting in 3-epi-25(OH)D 3 synthesis, are engaged in the catabolism of VD in BC patients, similar to healthy subjects.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The presented results provide evidence that both catabolic pathways, via 24-hydroxylase enzyme into 24,25(OH) 2 D and 1,24,25(OH) 3 D, considered as inert metabolites, and via C3-epimerase catabolic pathway [ 22 , 23 ] resulting in 3-epi-25(OH)D 3 synthesis, are engaged in the catabolism of VD in BC patients, similar to healthy subjects.…”
Section: Discussionmentioning
confidence: 66%
“…Vitamin D is catabolized mainly by the transformation of 1,25(OH) 2 D and its precursor 25(OH)D via 24-hydroxylase enzyme into 24,25(OH) 2 D and 1,24,25(OH) 3 D derivatives, known as inactive metabolites. Far less information is available about the function of the C 3 -epimerase catabolic pathway [ 22 , 23 ], resulting in 3-epi-25(OH)D 3 synthesis. However, due to different impacts on calcium and bone metabolism [ 24 ], distinguishing between 25(OH)D 3 and the C-3 epimer is considered of biological importance [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…6C, we examined the gene expression of several anti-inflammatory cytokines (Il4, Il10) and pro-inflammatory cytokines (Tnfa, Il17b, Il6, and Il1b) in the spleen, which was the tissue with the highest 1,25(OH) 2 D 3 concentration demonstrated by both MSI and confirmatory tissue homogenate. 1,25(OH) 2 D 3 has been shown to suppress the proinflammatory cytokines like Tnfa and Il17b and increase anti-inflammatory cytokines like Il4 and Il10 in macrophages and T cells during polarization, inflammatory disease, and cell differentiation (31)(32)(33)(34). We found that Il4 was significantly increased in the spleen, whereas Tnfa was suppressed.…”
Section: Gene Expression Consequences Of Elevated Tissue 125(oh) 2 Dmentioning
confidence: 60%
“…Применительно к дендритным клеткам и тканевым макрофагам эффекты лиганд-ассоциированной активации VDR в наибольшей степени изучены, среди всех иммунокомпетентных клеток, однако, опять же большинство представленных в литературе данных не основывается непосредственно на изменениях, касающихся пародонта. Одной из предпосылок к подобному детальному изучения данных популяций клеток стало выявление в них экспрессии рецептора витамина D, а также доказательство способности этих клеток локально синтезировать активную форму витамина D за счет гидроксилаз CYP27B1 и CYP24A1 [ 53,54 ] . И то, и другое свидетельствует в пользу глубокой сопряженности лиганд-ассоциированных эффектов VDR с функциональной ролью дендритных клеток и макрофагов в качестве антигенпредставляющих клеток и клетокинициаторов адаптивного иммунного ответа.…”
Section: дендритные клетки и тканевые макрофагиunclassified